Analisis Efektivitas dan Kontribusi Pajak Hotel, Pajak Restoran, dan Pajak Penerangan Jalan sebagai Sumber Pendapatan Asli Daerah Kabupaten Gresik Tahun 2016-2020 - Della Putri Veronika; Fajar Syaiful Akbar (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This research aims to prove “the level of effectiveness of tax collection for hotels, restaurants, street lighting and their contribution to PAD in Gresik Regency”. Quantitative descriptive is applied in this study. The object of research is “the Regional Revenue, Financial and Asset Management Agency of Gresik Regency”. The population in this study is “the Gresik Regency Government Financial Report 2016-2020”. The sample in this research is using “a report on the realization of the Hotel Tax, Restaurant Tax, Street Lighting Tax, and Local Revenue (PAD) budget realization reports in Gresik Regency in 2016-2020”. The sampling technique is using the purposive sampling method. The type of data used in this research is secondary data. The collection method uses documentation and literature study. The data analysis technique used in this research is quantitative descriptive. The research findings show that on average the effectiveness of collecting hotel taxes, restaurant taxes, and street lighting taxes in Gresik Regency is very effective and the average contribution of hotel collection and restaurant taxes is considered very less and street lighting taxes are considered moderate. Keywords: Effectiveness, Contribution, Tax, Local Revenue